Therapeutic Potential of CUDC-907 (Fimepinostat) for Hepatocarcinoma Treatment Revealed by Tumor Spheroids-Based Drug Screening - Liao, Wei; Yang, Wanren; Xu, Jiecheng; Yan, Zhengming; Pan, Mingxin; Xu, Xiaoping; Zhou, Shuqin; Zhu, Yu; Lan, Jianqiang; Zeng, Min; Han, Xu; Li, Shao; et al. (Frontiers in Pharmacology, 2021)
Background: Cancer is the second leading cause of death globally. However, most of the new anti-cancer agents screened by traditional drug screening methods fail in the clinic because of lack of efficacy. Choosing an appreciate in vitro tumor model is crucial for the preclinic drug screening. In this study, we screened anti-hepatocarcinoma (HCC) drugs by using a homemade spheroid cell culture device. Methods: Four HCC cell lines were three-dimensional (3D) cultured to screen 19 small molecular agents. 3D cultured primary HCC cells and tumor-bearing mice model were established to verify the candidate anti-hepatocarcinoma agent. Cell function experiments and western blotting were conducted to explore the anti-hepatocarcinoma mechanism of the candidate agent. Results: We found that CUDC-907 can serve as a potent anti-hepatocarcinoma agent. The study data show that CUDC-907 (fimepinostat), a novel dual acting inhibitor of phosphoinositide 3-kinase (PI3K) and histone deacetylase (HDAC), has potent inhibitory effects on HCC cell lines and primary HCC cells in vitro, Animal studies have shown that CUDC-907 can also suppress HCC cells in vivo. Furthermore, we found that CUDC-907 inhibits the PI3K/AKT/mTOR pathway and downregulates the expression of c-Myc, leading to the suppression of HCC cells. Conclusion: Our results suggest that CUDC-907 can be a candidate anti-HCC drug, and the 3D in vitro drug screening method based on our novel spheroid culture device is promising for drug screening.